2008
DOI: 10.1111/j.1365-2036.2008.03820.x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: the evidence base for long‐term management of coeliac disease

Abstract: SUMMARY BackgroundWhile gluten-free diet is an effective treatment for coeliac disease, the need for and goals of long-term management of patients are poorly defined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
146
2
9

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(161 citation statements)
references
References 341 publications
(225 reference statements)
4
146
2
9
Order By: Relevance
“…Furthermore, assessment of the level of non-adherence at which possible interventions would be deemed to be most beneficial is also problematic, as the potential individual and societal health benefit of small changes in gluten consumption is difficult to estimate. The risk of malignancy, for example, is now believed to be much lower than previously estimated and the influence of occasional non-adherence is unclear (Akobeng & Thomas, 2008;Catassi et al, 2007;Green et al, 2003;Haines, Anderson, & Gibson, 2008;Kaukinen et al, 1999;Silano et al, 2007). Diagnostic delay may have an influence on the likelihood of long term complications beyond treatment adherence (Silano et al, 2007) although the evidence for this is mixed (Haines et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, assessment of the level of non-adherence at which possible interventions would be deemed to be most beneficial is also problematic, as the potential individual and societal health benefit of small changes in gluten consumption is difficult to estimate. The risk of malignancy, for example, is now believed to be much lower than previously estimated and the influence of occasional non-adherence is unclear (Akobeng & Thomas, 2008;Catassi et al, 2007;Green et al, 2003;Haines, Anderson, & Gibson, 2008;Kaukinen et al, 1999;Silano et al, 2007). Diagnostic delay may have an influence on the likelihood of long term complications beyond treatment adherence (Silano et al, 2007) although the evidence for this is mixed (Haines et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This haplotype is also associated with type 1 diabetes, Addison syndrome, and Sjögren's syndrome (Haines, Anderson, & Gibson, 2008). Homozygocity for the HLA phenotypes is much more efficient at expressing antigens to gluten than heterozygous HLA, which may explain the varying degree and severity of symptoms in active celiac disease (Vader, et al, 2003).…”
Section: Chapter II Review Of Literature Celiac Diseasementioning
confidence: 99%
“…Serological testing relies on antibodies produced in response to gluten ingestion. Recent advances in serological antibody testing have shown that celiac disease is much more common than once thought (Haines, et al, 2008).…”
Section: Chapter II Review Of Literature Celiac Diseasementioning
confidence: 99%
“…Long-term complications of untreated CD are among others diarrhoea, abdominal pain, perinatal problems, osteoporosis and cancer. 1,4 CD has a strong genetic component, as 90% of CD patients carry the class II HLA-DQ2 haplotype, about 5% the HLA-DQ8 molecule [5][6][7][8] and the rest usually the half of the HLA-DQ2 heterodimer.The HLA-DQ2 and DQ8 haplotypes are present in over 25% of the general population, 6 but only 1% actually develops CD. 1 This indicates that HLA-DQ2 and -DQ8 haplotypes are necessary but not sufficient for disease development.…”
mentioning
confidence: 99%